An introgressed wing pattern acts as a mating cue (2015)
Heliconius butterflies provide good examples of both homoploid hybrid speciation and ecological speciation. In particular, examples of adaptive introgression have been detected among the subspecies of Heliconius timareta, which acquired red color pattern elements from H. melpomene. We tested whether the introgression of red wing pattern elements into H. timareta florencia might also be associated with incipient reproductive isolation (RI) from its close relative, H. timareta subsp. nov., found in the eastern Andes. No choice experiments show a 50% reduction in mating between females of H. t. subsp. nov. and males of H.t. florencia, but not in the reciprocal direction. In choice experiments using wing models, males of H. timareta subsp. nov. approach and court red phenotypes less than their own, whereas males of H. t. florencia prefer models with a red phenotype. Intrinsic postzygotic isolation was not detected in crosses between these H. timareta races. These results suggest that a color pattern trait gained by introgression is triggering RI between H. timareta subsp. nov. and H. t. florencia. © 2015 The Society for the Study of Evolution.